Long-term satellite tracking reveals variable seasonal migration strategies of basking sharks in the north-east Atlantic - Doherty, PD; Baxter, JM; Gell, FR; Godley, BJ; Graham, RT; Hall, G; Hall, J; Hawkes, LA; Henderson, SM; Johnson, L; Speedie, C; Witt, MJ (Scientific Reports, 2017)
Article This is the author accepted manuscript. The final version is available from Nature Publishing Group via the DOI in this record. Animal migration is ubiquitous in nature with individuals within a population often exhibiting varying movement strategies. The basking shark (Cetorhinus maximus) is the world’s second largest fish species, however, a comprehensive understanding of their long-term wider-ranging movements in the north-east Atlantic is currently lacking. Seventy satellite tags were deployed on basking sharks over four years (2012–2015) off the west coast of Scotland and the Isle of Man. Data from 28 satellite tags with attachment durations of over 165 days reveal post-summer ranging behaviours. Tagged sharks moved a median minimum straight-line distance of 3,633 km; achieving median displacement of 1,057 km from tagging locations. Tagged individuals exhibited one of three migration behaviours: remaining in waters of UK, Ireland and the Faroe Islands; migrating south to the Bay of Biscay or moving further south to waters off the Iberian Peninsula, and North Africa. Sharks used both continental shelf areas and oceanic habitats, primarily in the upper 50–200 m of the water column, spanning nine geo-political zones and the High Seas, demonstrating the need for multi-national cooperation in the management of this species across its range. Tagging in Scotland was funded by Scottish Natural Heritage and the University of Exeter. We extend our sincere thanks to the skippers and crew of the Sula Crion and Bold Ranger of Sealife Surveys, Tobermory. The attachment of satellite transmitters in Scottish coastal waters was regulated by the UK HM Government Home Office under the Animals (Scientific Procedures) Act 1986 (Project Licence 30/2975) and under the Wildlife & Countryside Act 1981 (as amended) (Licence(s): 13904, 13937 and 13971). The Manx Basking Shark Watch gives sincere thanks for support from the Manx Wildlife Trust and for funding from The Manx Lottery Trust, The Department of ...